Effect of non-invasive fractional photothermolysis on the efficacy of transdermal photosensitization in the experiment in vivo - D. I. Chernopyatov; N. P. Bgatova; S. D. Nikonov; V. V. Nimaev (Biomedical Photonics)
In an in vivo pilot study, the efficiency of noninvasive fractional laser photothermolysis (NFLP) as a transdermal system for application photosensitization of mouse skin before photodynamic therapy (PDT) was studied. For NFLP, a laser (λ = 970 nm) with an average power of 4 W and a pulse frequency of 50 Hz was used. An area of the skin of the anterior abdominal wall of mice was irradiated. After NFLP, a photosensitizer (PS) based on chlorin e6 in the form of a gel (0.5%) was applied to the skin with an application time of 30 min. Then, laser PDT (λ = 662 nm) was performed with a power of 2 W in a scanning pulse-periodic mode with a frequency of 5 Hz and a light spot area on the skin of 1.2 mm². The results of histological examination, confocal and electron microscopy showed the features of transdermal distribution of chlorin e6 after NFLP. PS fluoresces in all skin layers and the subcutaneous fat layer, indicating its deep penetration into the hypodermis after NFLP compared to conventional cutaneous application. The advantages of NFLP as a transport system for successful penetration of the gel form of chlorin e6 through all skin layers are demonstrated. Electron microscopy showed transdermal transport of PS in the form of nanosized microspheres and particles absorbed by macrophages and fibroblasts. It was also shown for the first time that pulsed PDT after NFLP leads to the formation of nanosized foci of photodestruction up to the border of the reticular layer of the skin and the hypodermis.